KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI ELPSA FRAMEWORK - Amalia, Dessy; Johar, Rahmah; Ikhsan, M. (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The mathematical communication ability of students is still low. One effort that can be done is to implement Experiences, Language, Pictures, Symbols, Application (ELPSA) framework. The pur pose of this research was to determine students' mathematical communication skills through the application of the ELPSA framework. This research is a descriptive quantitative research. The sub jects were Year 8 students of one of Junior High School in Banda Aceh which consisted of 24 students. Data collection is done through stdeunts worksheet and mathematical communication tests. Data ana lysis was performed by calculating the score of students' mathematical communication in groups and individually using percentage techniques. The results of this research are the mathematical com munication abilities of students in groups during learning with the implementation of ELPSA framework producing high average score. Whereas students' mathematical communication skills after the implementation of the ELPSA framework showed 75% of students met the minimal criteria.